1991
DOI: 10.3109/00498259109044406
|View full text |Cite
|
Sign up to set email alerts
|

Malaria infection impairs glucuronidation and biliary excretion by the isolated perfused rat liver

Abstract: 1. The effect of the erythrocyte stage of malaria infection on hepatic glucuronidation, biliary excretion and oxidation processes was investigated using harmol, salbutamol, taurocholate and propranolol. Livers from rats infected with the rodent malaria parasite P. berghei were isolated and perfused in a single-pass (harmol, taurocholate, propranolol) or recirculating (harmol, salbutamol) design. The degree of erythrocytic parasitaemia ranged from 16% to 63%. 2. The hepatic clearance (Cl) of harmol decreased fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Oxygen consumption in control IPRLs was similar throughout the experiments, albeit slightly lower than in some previous studies (normally at least 1.9 mmol O 2 min 71 g 71 liver (Gores et al, 1986;Cheung et al, 1996)). As in previous reports (Mansor et al, 1990;Murdoch et al, 1991Murdoch et al, , 1992, indices of liver viability were aected by MI, with bile¯ow and oxygen consumption signi®cantly lower in MI compared to control livers (Tables 1 and 2). Overall, these data con®rm that the experimental conditions for our IPRL studies were acceptable.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Oxygen consumption in control IPRLs was similar throughout the experiments, albeit slightly lower than in some previous studies (normally at least 1.9 mmol O 2 min 71 g 71 liver (Gores et al, 1986;Cheung et al, 1996)). As in previous reports (Mansor et al, 1990;Murdoch et al, 1991Murdoch et al, , 1992, indices of liver viability were aected by MI, with bile¯ow and oxygen consumption signi®cantly lower in MI compared to control livers (Tables 1 and 2). Overall, these data con®rm that the experimental conditions for our IPRL studies were acceptable.…”
Section: Discussionsupporting
confidence: 61%
“…Since MI and control livers had comparable cellular volumes, it was likely that metabolic rather than structural changes to the liver were responsible for impaired clearance of DHA. MI is known to decrease the cytochrome P450 content in rat liver microsomes (McCarthy et al, 1970) and has been shown in the IPRL model to reduce the clearance of several drugs, including the quinoline antimalarials and xenobiotics that are metabolised by glucuronidation (Mihaly et al, 1987;Mansor et al, 1990;Murdoch et al, 1991Murdoch et al, , 1992Glazier et al, 1994). Biliary clearance of DHA-glucuronide, the principal biliary metabolite of DHA (Maggs et al, 1997), also was impaired in MI (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in humans and experimental rodent models have reported malaria-induced alterations in the hepatic metabolism and clearance of numerous drugs, including many that are used in the treatment of malaria (Mihaly et al, 1987;Mansor et al, 1990;Murdoch et al, 1991;Pukrittayakamee et al, 1997). In mice, malaria infection is associated with decreases in the hepatic expression of CYP3A11 and other drug metabolizing enzymes (DMEs) (De-Oliveira et al, 2006;Carvalho et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…min -1. kg-1), the elimination half-life (Malaria, 3.8; Convalescence, 3.7 h) and apparent volume of distribution (Malaria, 1.2; Convalescence, 1.2; 1. kg -1) of paracetamol were similar during malaria and convalescence. In addition, the urinary excretion of paracetamol and its major phase II metabolites and their formation clearances from paracetamol were not significantly different between the two study phases.These data show that clinical malaria infection has no effect on the conjugation of paracetamol in man.Key words Paracetamol, Malaria; pharmacokinetics, phase II conjugation, glucuronidation, sulphation Hepatic phase II conjugation reactions are known to be reduced by experimental malaria infections in animals and perfused organ systems [1,2,3,4]. The aim of this investigation was to study the influence of clinical malaria on phase II conjugation reactions in man using paracetamol as a probe.…”
mentioning
confidence: 99%